Neutrophil Gelatinase–Associated Lipocalin as an Early Marker of Contrast‐Induced Nephropathy After Elective Invasive Cardiac Procedures - Kafkas, Nikolaos (Clin Cardiol, 2016)
BACKGROUND: Contrast‐induced nephropathy (CIN) is an acute kidney injury (AKI) defined as serum creatinine (sCr) increase 48 to 72 hours after contrast administration. Because most subjects undergoing invasive cardiac procedures are discharged within 24 hours, sCr is unsuitable for CIN detection. HYPOTHESIS: In the present study we tested the hypothesis that neutrophil gelatinase‐associated lipocalin (NGAL) is superior compared with sCr and other established nephropathy markers in early CIN diagnosis after elective invasive cardiac procedures. METHODS: Serum creatinine, urine creatinine, serum cystatin C, urine albumin, urine NGAL (uNGAL), and plasma NGAL were measured at 0, 6, 24, and 48 hours after contrast administration in 100 elective invasive cardiac procedures. Estimated glomerular filtration rate and albumin‐to‐creatinine ratio were calculated. Changes from baseline were considered statistically significant at P < 0.05 and clinically significant when > the biomarker's reference change value. Participants were divided into those with and without clinically significant uNGAL changes (uNGAL positive and negative for AKI, respectively). RESULTS: Thirty‐three individuals were uNGAL positive for AKI. Serum cystatin C changes were statistically and clinically nonsignificant in both groups. Serum creatinine and plasma NGAL were statistically but not clinically elevated 48 hours postcatheterization in the AKI group. Except for contrast volume (higher in AKI group), groups were comparable at baseline (P not significant) regarding cardiovascular risk factors, coronary heart disease, coronary interventions performed, and renal biomarkers. Baseline uNGAL was significantly correlated to estimated glomerular filtration rate and albumin‐to‐creatinine ratio. CONCLUSIONS: Urine NGAL is potentially superior compared with conventional nephropathy markers in early CIN diagnosis after elective invasive cardiac procedures. Definition of clinically significant uNGAL changes with reference change value is probably a valuable supplement to statistically defined significant variations.